Evaluation of the microbial safety of commercially produced tomatoes in South Africa and the development of a novel enrichment broth for the identification of Escherichia coli O157:H7 - Korsten, Lise (University of Pretoria, 2016)
Dissertation (MSc)--University of Pretoria, 2015.